Circular RNAs as a novel class of potential therapeutic and diagnostic biomarkers in reproductive biology/diseases - Wanyu Song; Xiuli Chen; Haiying Wu; Neda Rahimian (European Journal of Medical Research)
Abstract Infertility is a prevalent problem among 10% of people within their reproductive years. Sometimes, even advanced treatment options like assisted reproduction technology have the potential to result in failed implantation. Because of the expected changes in gene expression during both in vitro and in vivo fertilization processes, these methods of assisting fertility have also been associated with undesirable pregnancy outcomes related to infertility. In this aspect, Circular RNAs (circRNAs) play a crucial role as epigenetic modifiers in a wide range of biological and pathological activities, including problems with fertility. CircRNAs are integral pieces in multiple cellular functions, including moving substances within the nucleus, silencing one X chromosome, cell death, the ability of stem cells to differentiate into different cell types, and the process of gene expression inherited from parental genes. Due to the progress made in high-speed gene sequencing, a large amount of circRNA molecules have been detected, revealing their significant functions in diverse biological functions like enhancing testicular development, preserving the differentiation and renewal of spermatogonial cells, and controlling spermatocyte meiosis. Moreover, these non-coding RNAs contribute in different aspects of female reproductive system including pregnancy-related diseases, gynecologic cancers, and endometriosis. In conclusion, there is no denying that circRNAs have immense potential to be used as biomarkers and treatments for reproductive disorders in males and females. In this research, we provide a comprehensive analysis of the multiple circRNAs associated with women’s infertility.